Azithromycin Versus Co-trimoxazole in The Treatment of Doxycycline Resistant Acne Vulgaris In Iraqi Patients - Fadheel, Basman M. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Acne is a multifactorial disease with multiple pathogenic factors. Many types of therapies are available including systemic antibiotics , choosing the appropriate one depend on the experience of the doctor , side effects , antimicrobial resistance , availability and cost. Although doxycycline is effective and commonly prescribed as first line systemic treatment for moderate to severe inflammatory acne vulgaris , some cases do not respond because of antimicrobial resistance.Objective: To evaluate and compare the effectiveness and safety of azithromycin and co-trimoxazole in the treatment of acne vulgaris cases that are resistant to doxycycline  in Iraqi patients.Patients and methods: A randomized clinical trial was carried out at the Department of Dermatology and Venereology of Baghdad Teaching hospital between April 2009 and October 2010.    A total of 50 patients with doxycycline resistant moderate to severe papulopustular  acne vulgaris were divided to two equal groups to receive either azithromycin or co-trimoxazole. Both groups received treatment for 2 months . in the first group azithromycin 250 mg was prescribed daily for 1 months and everyother day for the second month. The second group received co-trimoxazole 960 mg twice daily for 2 months. The clinical assessment was done by counting the number of inflammatory lesions at 3 occasions : baseline ,after 1 month and after 2 months . Patients also seen after 2 months of cessation of therapy to asses the relapse rate.Results: After 2 months both groups show statistically significant difference from the base line in reducing the number of inflammatory lesions and improving acne but azithromycin was superior to co-tomoxazole.Conclusion: This study showed that both azithromycin and co-trimoxazole are effective and safe alternative drugs in the treatment of doxycycline resistant acne vulgaris . But Azithromycin is more effective with less relapse rate and better compliance, but it is more costy than co-trimoxazole . Co-trimoxazole is safe and good alternative option   in treating doxycycline resistant acne vulgaris.